PENERAPAN MANAJEMEN PENGETAHUAN PADA APLIKASI WEB CHAT BERBASIS WEB DI PT.SINAR MITRA SEPADAN FINANCE - Reo Wijaya (Jurusan Teknik Informatika, 2012)
Along with the times when technology is growing rapidly, as well as increased competition among business firms then the need for the application of knowledge management concepts that are implemented into a web chat application that is expected to assist the company in terms of communication delivery. Method of this thesis is FAST (Framework for the Application of Systems Thinking), which consists of several phases of system developers. The first phase of the scope of the definition of directly observing the company's operational processes, the second phase of the analysis of problems occurring within the company, the third phase of requirements analysis using the framework Pieces, the four phases of decision analysis provides an assessment and recommendations contained in the system. These five logical design phase to design the system in the form of data flow diagrams, flowcharts, data tables, and ERD, the sixth phase of the construction and testing program has been completed, the seventh phase of the implementation of the system by running and training. This application is designed using PHP as a software application program, and MySQL as the database. The results of this analysis are expected to help the communication process that occurs and is able to shorten the time in terms of work related to communication processes that exist within the company.